Impacto del COVID- 19 en las actividades económicas-financieras de las cooperativas de Ahorro y Crédito del Segmento Dos - Bravo Vera, Jenniffer Janeth (2022)
The main objective of this research work was to analyze the impact of COVID-19 on the economic-financial activities of the Ecuadorian savings and credit cooperatives of segment two, being able to identify variations in the historical data of the financial statements from the year 2017 to the year 2021. A total of 22 entities from segment two were taken as a population sample that reported uninterruptedly to the Superintendency of Popular Solidarity Economy the accounting information necessary to be evaluated, cross-sectional, causal, bibliographic, exploratory and quantitative research was used, while the methods used were analytical and descriptive, on the other hand, among the required techniques, the bibliographic review, financial analysis and forecasts stand out, in turn the PEARLS monitoring system was used as a tool. To obtain the results, three methodological phases were structured, in the first the horizontal and vertical analysis of the balance sheet and income statement was carried out for the comparison between the historical data, the second phase consisted of the calculation and analysis of the financial indicators established by the PEARLS methodology for the identification of the variations of the last four years and in the third phase the financial indicators were projected to determine the future behavior of the data in relation to the last years. This work concludes with the identification of the negative impact on the economic-financial activities of the COACs of segment two during the year 2020 in relation to the year prior to the pandemic and observing improvement in the year 2021